PERTIMBANGAN HAKIM DALAM MENGABULKAN PERMOHONAN POLIGAMI DI PENGADILAN AGAMA SURAKARTA (STUDI KASUS PUTUSAN NOMOR : 0373/PDT.G/2013/PA.SKA.) - , Eva Nur Aryati, Muhammad Mukti Ali (Fakultas Hukum Universitas Sebelas Maret, 2014)
Abstract This research aims to find out the reasoning of judges in decided the matter of polygamy in Surakarta Religious Court. This research includes normative research type which are prescriptive. The data of this research includes primary data and secondary data. Secondary data is the main data in this research. To collect secondary data used with literature study or documents study. Analytical techniques used are qualitative. The basic of this analysis is deductive, ways of drawing conclusions from things that are common to the direction of the things that are specific. Based on this research, can be concluded that the judge set aside the Article 4 paragraph (2) of Law Number Â 1 of 1974 which is the legal basis of facultative requirement in the case of polygamy. Judges apply the Article 5 paragraph (1) of Law Number 1 of 1974 as a cumulative requirement and using the benefit principle to accept the application of poligamy. Key words: Poligamy, Polygamy Requirements, Befenit